Use of the Internet at the University of Baghdad (Journal of the College of Basic Education, 2023)
This study aims to identify how the Internet is used by Baghdad University students.The sample size was (300) male and female students. In this study, a questionnaire prepared byThe research consists of (27) paragraphs. The results indicated that university students use the Internet.For social purposes in the first place, then for general purposes, and finally for scientific purposes. And he ledThe study found that there are significant statistical differences under the level of 0.05 between male and female students.There are also differences between the students of the science and humanities departments. The study recommended several constructive recommendations.on the search results.Research problemThe concept of information has been known to man in the past, and this is evident through the writingsand the inscriptions found in the clay tablets found in the civilization of the Al-Arfidian Valley.The concept has become very popular recently as a result of the multiplicity of information and the accompanying tremendous development of information transfer.and its treatment. The increasing influence of technological sciences on people made what they were doingLibraries of collecting, organizing and preserving intellectual production are not sufficient, and this is howThe need to provide information services at a level that meets the needs of the researcher who requestsexpress service. The advent of the Internet as a means of communication through which millions ofdirect and indirect, as individuals can communicate with each other by addressingWritten conversation (chat) and voice communication over the phone via the Internet. They can alsoIndirect communication via e-mail, in addition to the many benefits thatHe presents it to the students, through which the student can enter the international libraries and reviewThe scientific output of researchers. The Internet is a repository that contains many books and scientific research.and audio and video lectures (Abdel-Fattah 1998), which allows the student to use a widefor information.